The hybrid smart contract agreement challenge to European electronic signature regulation. (26th May 2020) - Veerpalu, Anne; Jürgen, Liisi; Rodrigues e Silva, Eduardo da Cruz; Norta, Alex
Abstract: The article investigates the smart contract used in the Initial Coin Offering (ICO) process and its qualification under the typology of form of contract and the EU electronic signature regulation eIDAS. 1 ICOs took the globe by storm in 2017 and created a lot of turmoil among the regulators due to a new form of raising funds globally. In addition to their effect on the capital market, another phenomenon that saw a rise in popularity was the smart contract. The smart contract is usually built into the ICO process as a protocol to execute the issue of a token. The article suggests that the contract in the ICO process does not only refer to the smart/contract code in silos but should be considered in the larger context as the so-called hybrid smart contract agreement with the smart contract protocol being merely the execution motor for the issuance of the token. The article qualifies the contract concluded during the ICO process under the general typology of forms of contract with the aim to identify whether the hybrid smart/contract agreement is in electronic form of contract. Some states in the USA and a few Member States in the EU have also introduced smart contract-specific regulation clearly stating that smart contracts are contracts either in electronic or written form. Still, as this is not prevalent in the EU law, the principle of functional equivalence is used to assess whether the signature on a smart contract used in an ICO process is functionally equivalent to the qualified electronic signature under eIDAS. The existence of a qualified electronic signature allows the contract to be qualified as a contract in electronic form equivalent to a paper-form agreement with hand-written signatures. Furthermore, the article investigates whether the centralized trust system of the eIDAS creates an infrastructural bias against the source of trust in case of distributed ledger technology that in itself could be non-compliant with the principle of technology neutrality.